Characterization of Flagellar Propulsion of Soft Microrobotic Sperm in a Viscous Heterogeneous Medium - Khalil, Islam S. M.; Klingner, Anke; Hamed, Youssef; Magdanz, Veronika; Toubar, Mohamed; Misra, Sarthak (Frontiers in Robotics and AI, 2019)
Several microorganisms swim by a beating flagellum more rapidly in solutions with gel-like structure than they do in low-viscosity mediums. In this work, we aim to model and investigate this behaviour in low Reynolds numbers viscous heterogeneous medium using soft microrobotic sperm samples. The microrobots are actuated using external magnetic fields and the influence of immersed obstacles on the flagellar propulsion is investigated. We use the resistive-force theory to predict the deformation of the beating flagellum, and the method of regularized Stokeslets for computing Stokes flows around the microrobot and the immersed obstacles. Our analysis and experiments show that obstacles in the medium improves the propulsion even when the Sperm number is not optimal. Experimental results also show propulsion enhancement for concentration range of 0-5% at relatively low actuation frequencies owing to the pressure gradient created by obstacles in close proximity to the beating flagellum with. At relatively high actuation frequency, speed reduction is observed with the concentration of the obstacles.